The Rape of Tamar as a Prefiguration for the Fate of Fair Zion - Adelman, Rachel (Journal of feminist studies in religion, 2021)
Daughters, as the most sheltered and vulnerable figures within the father's household, present the most poignant critique of that household when it comes undone. The story of the rape of Tamar, King David's daughter, by her half-brother Amnon (2 Sam 13:1-20), is read not only as the beginning of the unraveling of the kingdom, but as a prefiguration of the fate of Bat Tzion (Daughter Zion or Fair Zion), the personification of Jerusalem, Temple, and the Judean people. Like Tamar, Bat Tzion is ravaged and left desolate (shomemah). Unlike her mortal sister, however, who is ultimately silenced, Bat Tzion is given voice in the poetry of lament and consolation (Lamentations and Second Isaiah). While engaging in a historical-contextual approach to the Hebrew Bible, with an emphasis on intertextuality, this article uncovers voices that challenge the patriarchal values imbedded in father-daughter relations in the Hebrew Bible.